2020
DOI: 10.3390/agronomy10020286
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora Antagonism of Endophytic Bacteria Isolated from Roots of Black Pepper (Piper nigrum L.)

Abstract: In this study, 90 root samples were collected from 30 black pepper farms in three provinces in the Central Highlands of Vietnam. A total of 352 endophytic bacteria were isolated and their morphology described. An in vitro assay on the antifungal activity of these isolates was then conducted and 47 isolates were found to have antagonistic activity on Phytophthora fungi. The antifungal activity of the 47 isolates was evaluated in vivo by shoot assay. Among these 47 isolates, 6 were selected for further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…Interestingly, this strain could inhibit up to 98.8% of Phytophthor growth by producing various enzymes and biochemical compounds; this was confirme by in vivo assays on the black pepper seedlings in the green house. We also carried out phylogenetic analysis of 352 endophytic bacteria isolated from 90 root samples in th farms in the Central Highlands of Vietnam for Phytophthora antagonism under in vitr assay conditions [36]. The results showed that Bacillus velezensis and Bacillus amylolique faciens exhibit pathogenic fungal antagonism and plant growth promotion activities Most studies have reported the results of rhizosphere bacteria and endophytic bacteri on the plant growth promotion and antifungal activity using in vitro or green house-based experiments [8,9,27,28,30,34,36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this strain could inhibit up to 98.8% of Phytophthor growth by producing various enzymes and biochemical compounds; this was confirme by in vivo assays on the black pepper seedlings in the green house. We also carried out phylogenetic analysis of 352 endophytic bacteria isolated from 90 root samples in th farms in the Central Highlands of Vietnam for Phytophthora antagonism under in vitr assay conditions [36]. The results showed that Bacillus velezensis and Bacillus amylolique faciens exhibit pathogenic fungal antagonism and plant growth promotion activities Most studies have reported the results of rhizosphere bacteria and endophytic bacteri on the plant growth promotion and antifungal activity using in vitro or green house-based experiments [8,9,27,28,30,34,36].…”
Section: Methodsmentioning
confidence: 99%
“…We also carried out phylogenetic analysis of 352 endophytic bacteria isolated from 90 root samples in th farms in the Central Highlands of Vietnam for Phytophthora antagonism under in vitr assay conditions [36]. The results showed that Bacillus velezensis and Bacillus amylolique faciens exhibit pathogenic fungal antagonism and plant growth promotion activities Most studies have reported the results of rhizosphere bacteria and endophytic bacteri on the plant growth promotion and antifungal activity using in vitro or green house-based experiments [8,9,27,28,30,34,36]. To date, few works have researched th impact of rhizosphere bacteria and endophytic bacteria on the growth and disease re sistance of black pepper in the field.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-fungal activity of Pseudomonas aeruginosa TUN03 was assessed according to the method per Ngo et al 2020 [33]. A total of 12 fungal pathogen strains (supported from the Institute of Biotechnology and Environment, Tay Nguyen University, Buon Ma Thuot, Vietnam), including Purpureocillium lilacinum F01, Fusarium solani F02, F. solani F03, F. solani F04, Colletotrichum gloeosporioides F05, F. incarnatum F06, Gongronella butleri F07, Pestalotiopsis mangiferae F08, F. incarnatum F09, F. oxysporum F10, Neonectria sp.…”
Section: Anti-fungal Assaysmentioning
confidence: 99%
“…Assessment of in vitro antifungal activity test of Pseudomonas aeruginosa TUN03 against various plant-pathogen fungal strains. : the activity was observed but not clear for harvesting the data based on the method reported by Ngo et al 2020[33]. All the experiments were performed in triplicate.…”
mentioning
confidence: 96%
“…The zoospores were not able to germinate when they were cultured in the presence of this compound. Ngo et al, (2020) [52] isolated endophytic black pepper bacteria, of which six showed the ability to inhibit the growth of Phytophthora spp. by more than 60%.…”
Section: Biocontrol Of Phytophthora Spp By Endophytic Bacteriamentioning
confidence: 99%